2009
DOI: 10.1111/j.1601-5223.1978.tb01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers in the Spitsbergen reindeer

Abstract: Blood samples from 81 Spitsbergen reindeer together with reference samples from 11 continental Norwegian reindeer have been examined by different electrophoretic techniques with regard to the following genetic marker systems: Red cells: Hb, PGM, 6‐PGD, GPT, ESD, GLO, and AcP. Serum: A1 and Tf. In all markers except Tf (transferrin) Spitsbergen reindeer types showed the same electrophoretic patterns as did the continental Norwegian reindeer, i.e. they probably were homozygous for the alleles seen in the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Extremely important data were obtained from the study of blood serum using this method. Thus, polyacrylamide gel electrophoresis was used to analyze transferrin variation in reindeer, which was described by Storset et al (1978), Baccus et al (1983), Roed (1985), Cronin (1995). Shubin (1969) found out that in Russia a transferrin locus in reindeer is represented by 13 genetic variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extremely important data were obtained from the study of blood serum using this method. Thus, polyacrylamide gel electrophoresis was used to analyze transferrin variation in reindeer, which was described by Storset et al (1978), Baccus et al (1983), Roed (1985), Cronin (1995). Shubin (1969) found out that in Russia a transferrin locus in reindeer is represented by 13 genetic variants.…”
Section: Resultsmentioning
confidence: 99%
“…Several genetic surveys have been conducted for reindeer, using diff erent genetic methods, such as, gel electrophoresis (Storset et al, 1978;Roed, 1985;Shubin, 1969), mitochondrial DNA markers (Flagstad and Røed, 2003;Cronin et al, 2005) and nuclear microsatellites (Ball et al, 2010;McDevitt et al, 2009;Zittlau et al, 2000;Wilson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recent morphometric and genetic studies have indicated that there is a close taxonomic affinity between Rangifer tarandus pearyi from the Canadian Arctic Islands, R. t. eogroenlandicur from Northeast Greenland and perhaps R. t. platyrhynchus from Svalbard (Hakala et al 1985;Rded 1985;Rded & Whitten 1986;). It has also been shown that there is comparatively little genetic similarity between the arcticisland caribou, on the one hand, and the Eurasian and mainland North American caribou and reindeer on the other (Storset et al 1978;Hakala et al 1985;Rded & Whitten 1986;Roe9 et al 1986).…”
Section: Morten Meldgaard and Ole Bennikementioning
confidence: 99%
“…Research began in the 1960s, when a simple and quick methods of electrophoresis in agar, starch and acrylamide gel were introduced in population genetics widely. Later, the studies of serum transferrin polymorphism were reported [13][14][15][16]. With the development of molecular genetics, application of more precise methods became possible for the direct analysis at the DNA level with a higher capacity as compared to the previously used marker systems [17,18].…”
Section: Introductionmentioning
confidence: 99%